Radiationless mechanism of UV deactivation by cuticle phenolics in plants - González Moreno, Ana; de Cózar, Abel; Prieto, Pilar; Domínguez, Eva; Heredia, Antonio (Nature communications, 2022)
Hydroxycinnamic acids present in plant cuticles, the interphase and the main protective barrier between the plant and the environment, exhibit singular photochemical properties that could allow them to act as a UV shield. Here, we employ transient absorption spectroscopy on isolated cuticles and leaf epidermises to study in situ the photodynamics of these molecules in the excited state. Based on quantum chemical calculations on p -coumaric acid, the main phenolic acid present in the cuticle, we propose a model in which cuticle phenolics display a photoprotective mechanism based in an ultrafast and non-radiative excited state deactivation combined with fluorescence emission. As such, the cuticle can be regarded as the first and foremost protective barrier against UV radiation. This photostable and photodynamic mechanism seems to be universal in land plants giving a special role and function to the presence of different aromatic domains in plant cuticles and epidermises. Phenolics are abundant in plant cuticles. Here, via transient absorption spectroscopy and quantum chemical calculations, the authors propose a model by which cuticle phenolics provide photoprotection due to ultrafast and non-radiative excited state deactivation combined with fluorescence emission.